Participação do sistema GABAérgico no mecanismo de ação anestésica dos óleos essenciais de Aloysia triphylla e Cymbopogon flexuosus em jundiás (Rhamdia quelen) - Santos, Alessandro Casale dos (2016)
This study demonstrated the sedative and anesthetic activity of the essential oil (EO) of Cymbopogon flexuosus in the silver catfish (Rhamdia quelen). The time for induction and recovery of this EO was compared with the EO of Aloysia triphylla, due to the similarity between their major components: α-citral (geranial) and β-citral (neral). Both EOs induced anesthesia at concentrations from 150 to 300 μL L-1 and sedation at 25 μL L-1. The EO of C. flexuosus was faster in inducing the initial stages of anesthesia, but there was no significant difference to reach deep anesthesia, and there was a significantly longer recovery time. Cooperative relations and the modulation of the benzodiazepine (BDZ) site of GABAa as a mechanism of action of both EOs was verified from the addition of diazepam and flumazenil to experiments (BDZ site of GABAa agonist and antagonist, respectively). The addition of diazepam (150 μM) induced potentiation in concentrations of 25, 150 and 300 μL L-1 both EOs without significant change in anesthesia recovery time. Flumazenil (10 μM) reversed the diazepam-induced anesthesia, but not the anesthesia induced by EOs at concentrations of 150 and 300 μL L-1, thus the EO of C. flexuosus induced effective sedation and anesthesia without short-term mortality and the modulation of the BDZ site of the GABAa in the anesthetic action mechanism of both EOs in this study was not demonstrated.